Enhanced polyethylene terephthalate (PET) glycolysis with biochar-supported organic ionic liquid-based catalysts - Stuart Conroy; Fraser Norris; Elliot Ross; Stuart D. Robertson; Yong Xu; Ashleigh J. Fletcher; Xiaolei Zhang (Journal of Environmental Chemical Engineering, 2026)

Mangrove organic matter accumulated recently at Low Isles, Great Barrier Reef - Brooke M. Conroy; Jeffrey J. Kelleway; Haidee Cadd; Sarah M. Hamylton; Colin D. Woodroffe; David P. Child; Michael A.C. Hotchkis; Quan Hua; Sabika Maizma; Patricia Gadd; Debashish Mazumder; Kerrylee Rogers (Estuarine, Coastal and Shelf Science, 2026)

Associations Between Sustainable Diet Scores and Sleep Health Indicators Among Mexican Women - A. Mohy; D. Su; K. Peterson; A. Jones; D. Conroy; A. Cantoral; M. Tellez-Rojo; L. Torres-Olascoaga; Y. Seo; E. Jansen (Journal of the Academy of Nutrition and Dietetics, 2025)

Prevalence of cannabis and medication use by indices of residential urbanicity and deprivation among Ohio cancer patients - Theodore M. Brasky; Shieun Lee; Bella McBride; Alison M. Newton; Ryan D. Baltic; Theodore L. Wagener; Sara Conroy; John L. Hays; Erin E. Stevens; Anita Adib; Jessica L. Krok-Schoen (Cancer Causes & Control, 2025)
Purpose There is increasing interest in the use of cannabis products to alleviate symptom burden among cancer patients. Although data remain limited, some evidence suggests that state legalization of cannabis is associated with reduced opioid use. Indices of area-level social determinants of health may provide insights into the patterns of symptom-managing behaviors in the context of health equity. Methods Residential ZIP codes from 854 Ohio residents diagnosed with invasive cancer at an academic cancer center were used to assign rural–urban commuting area (RUCA) codes and social deprivation index (SDI) values. RUCA was categorized as metropolitan and non-metropolitan, and SDI was dichotomized at the median. Participants completed a one-time cannabis-focused questionnaire which included items on medications used to alleviate symptoms. Results The prevalence of self-reported cannabis (19% vs. 13%) and opioid use (30% vs. 21%) were higher among patients living in areas of higher social disadvantage vs. lower. No differences were observed for use of benzodiazepines or for any product by residential urbanicity. Conclusion Larger, multi-institutional studies with detailed measurement of cannabis and medications and an increased capacity to examine additional social determinants of health are needed to confirm and explain these descriptive findings.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Territorial and occupancy behavior of black sea bass on oyster aquaculture gear and boulder habitat - Adam D. Armbruster; Renee Mercaldo-Allen; Julie M. Rose; Kristen Seda; Paul Clark; Gillian Phillips; Dylan Redman; Christian W. Conroy (Frontiers in Marine Science, 2024)
Observations of fish behavior can provide insights into habitat preferences and use. Black sea bass, Centropristis striata , are a territorial temperate reef finfish species known for their high commercial and recreational value and association with structured habitat. We used underwater action cameras to record video of black sea bass to assess territorial (agonistic, ambush, displacement) and occupancy (station-keeping) behaviors on shelf and bag style oyster aquaculture cages at a shellfish farm, and on boulders at a natural rock reef near Milford, Connecticut in Long Island Sound, Northwest Atlantic. Black sea bass at a variety of life stages were highly associated with cages, including young-of-the-year, and age 1+ fish. The high abundance of black sea bass observed on cages relative to boulders suggests this species has an affinity for the vertical structure created by aquaculture gear. When behaviors were normalized to the total fish sightings, black sea bass showed no significant difference in frequency of behaviors between habitats, indicating that per-fish rates of behavior were similar on cages and boulders. Demonstration of territorial and occupancy behaviors by black sea bass on, and around cages suggests that aquaculture gear provides structured habitat and ecosystem services for this species similar to natural reefs.These results suggest that essential fish habitat descriptions of manmade structures used by black sea bass could be broadened to include aquaculture gear. Our study provides novel information on behavioral interactions of black sea bass with oyster cages that may support aquaculture permitting and consultation processes.

Modeling mate choice in a small-scale community: Applying couple simulation in the U.S. and Conambo, Ecuador - Daniel Conroy-Beam; John Q. Patton; Cari D. Goetz; Aaron W. Lukaszewski; Brenda Bowser (Evolution and Human Behavior, 2023)

Disparities in cause-specific mortality by race and sex among bladder cancer patients from the SEER database - Timothy D. Shu; Fredrick R. Schumacher; Britt Conroy; Lee Ponsky; Amr Mahran; Laura Bukavina; Adam Calaway; Sarah C. Markt (Cancer Causes & Control, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Comparison of Single and Repeated Dosing of Anti-Inflammatory Human Umbilical Cord Mesenchymal Stromal Cells in a Mouse Model of Polymicrobial Sepsis - Barbara Fazekas; Senthilkumar Alagesan; Luke Watson; Olivia Ng; Callum M. Conroy; Cristina Català; Maria Velascode Andres; Neema Negi; Jared Q. Gerlach; Sean O. Hynes; Francisco Lozano; Stephen J. Elliman; et al. (Stem Cell Reviews and Reports, 2022)
Summary Mesenchymal stromal cells (MSCs) ameliorate pre-clinical sepsis and sepsis-associated acute kidney injury (SA-AKI) but clinical trials of single-dose MSCs have not indicated robust efficacy. This study investigated immunomodulatory effects of a novel MSC product (CD362-selected human umbilical cord-derived MSCs [hUC-MSCs]) in mouse endotoxemia and polymicrobial sepsis models. Initially, mice received intra-peritoneal (i.p.) lipopolysaccharide (LPS) followed by single i.p. doses of hUC-MSCs or vehicle. Next, mice underwent cecal ligation and puncture (CLP) followed by intravenous (i.v.) doses of hUC-MSCs at 4 h or 4 and 28 h. Analyses included serum/plasma assays of biochemical indices, inflammatory mediators and the AKI biomarker NGAL; multi-color flow cytometry of peritoneal macrophages (LPS) and intra-renal immune cell subpopulations (CLP) and histology/immunohistochemistry of kidney (CLP). At 72 h post-LPS injections, hUC-MSCs reduced serum inflammatory mediators and peritoneal macrophage M1/M2 ratio. Repeated, but not single, hUC-MSC doses administered at 48 h post-CLP resulted in lower serum concentrations of inflammatory mediators, lower plasma NGAL and reversal of sepsis-associated depletion of intra-renal T cell and myeloid cell subpopulations. Hierarchical clustering analysis of all 48-h serum/plasma analytes demonstrated partial co-clustering of repeated-dose hUC-MSC CLP animals with a Sham group but did not reveal a distinct signature of response to therapy. It was concluded that repeated doses of CD362-selected hUC-MSCs are required to modulate systemic and local immune/inflammatory events in polymicrobial sepsis and SA-AKI. Inter-individual variability and lack of effect of single dose MSC administration in the CLP model are consistent with observations to date from early-phase clinical trials. Graphical Abstract

What Does the Public Believe about Tall Wood Buildings? An Exploratory Study in the US Pacific Northwest - Pipiet Larasatie; Jose E Guerrero; Kendall Conroy; Troy E Hall; Eric Hansen; Mark D Needham (Journal of Forestry, 2018)

Habitat Associations of Juvenile Cod in Nearshore Waters - Jonathan H. Grabowski; Christian W. Conroy; Rachel K. Gittman; Joseph T. Kelley; Sally Sherman; Graham D. Sherwood; Gail Wippelhauser (Reviews in Fisheries Science & Aquaculture, 2018)

Further insights into the responses of macroinvertebrate species to burial by sediment - E. Conroy; J. N. Turner; A. Rymszewicz; M. Bruen; J. J. O’Sullivan; D. M. Lawler; S. Stafford; M. Kelly-Quinn (Hydrobiologia, 2018)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Chemotherapy-induced amenorrhea: a prospective study of brain activation changes and neurocognitive correlates - Susan K. Conroy; Brenna C. McDonald; Tim A. Ahles; John D. West; Andrew J. Saykin (Brain Imaging and Behavior, 2013)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

“Dead Zone” dynamics in Lake Erie: the importance of weather and sampling intensity for calculated hypolimnetic oxygen depletion rates - Joseph D. Conroy; Leon Boegman; Hongyan Zhang; William J. Edwards; David A. Culver (Aquatic Sciences, 2011)

Marine mammal and seabird summer distribution and abundance in the fjords of northeast Cumberland Sound of Baffin Island, Nunavut, Canada - Kristen M. Diemer; Michael J. Conroy; Steven H. Ferguson; Donna D. W. Hauser; Alice Grgicak-Mannion; Aaron T. Fisk (Polar Biology, 2011)

Exposure to preindustrial, current and future atmospheric CO 2 and temperature differentially affects growth and photosynthesis in Eucalyptus - OULA GHANNOUM; NATHAN G. PHILLIPS; JANN P. CONROY; RENEE A. SMITH; RENEE D. ATTARD; ROSLYN WOODFIELD; BARRY A. LOGAN; JAMES D. LEWIS; DAVID T. TISSUE (Global Change Biology, 2010)
To investigate if Eucalyptus species have responded to industrial‐age climate change, and how they may respond to a future climate, we measured growth and physiology of fast‐ ( E. saligna ) and slow‐growing ( E. sideroxylon ) seedlings exposed to preindustrial (290), current (400) or projected (650 μL L −1 ) CO 2 concentration ([CO 2 ]) and to current or projected (current +4 °C) temperature. To evaluate maximum potential treatment responses, plants were grown with nonlimiting soil moisture. We found that: (1) E. sideroxylon responded more strongly to elevated [CO 2 ] than to elevated temperature, while E. saligna responded similarly to elevated [CO 2 ] and elevated temperature; (2) the transition from preindustrial to current [CO 2 ] did not enhance eucalypt plant growth under ambient temperature, despite enhancing photosynthesis; (3) the transition from current to future [CO 2 ] stimulated both photosynthesis and growth of eucalypts, independent of temperature; and (4) warming enhanced eucalypt growth, independent of future [CO 2 ], despite not affecting photosynthesis. These results suggest large potential carbon sequestration by eucalypts in a future world, and highlight the need to evaluate how future water availability may affect such responses.

A new microtubule-targeting compound PBOX-15 inhibits T-cell migration via post-translational modifications of tubulin - Navin K. Verma; Eugene Dempsey; Jennifer Conroy; Peter Olwell; Anthony M. Mcelligott; Anthony M. Davies; Dermot Kelleher; Stefania Butini; Giuseppe Campiani; D. Clive Williams; Daniela M. Zisterer; Mark Lawler; et al. (Journal of Molecular Medicine, 2008)

Effects of leaf and branch removal on carbon assimilation and stem wood density of Eucalyptus grandis seedlings - D. S. Thomas; K. D. Montagu; J. P. Conroy (Trees, 2006)

Microsatellite Variation in Two Populations of Free-Ranging Yellow Baboons (Papio hamadryas cynocephalus) - D. St. George; S. M. Witte; T. R. Turner; M. L. Weiss; J. Phillips-Conroy; E. O. Smith; J. Rogers (International Journal of Primatology, 1998)

Imperata management strategies used in smallholder rubber-based farming systems - H. Bagnall-Oakeley; C. Conroy; A. Faiz; A. Gunawan; A. Gouyon; E. Penot; S. Liangsutthissagon; H. D. Nguyen; C. Anwar (Agroforestry Systems, 1996)